The synergetic effect of alcohol consumption and cigarettes per day on smoking outcomes expectancies among Latinx adult smokers. Issue 3 (4th August 2022) - Rodriguez-Cano, Ruben; Garey, Lorra; Bakhshaie, Jafar; Shepherd, Justin M.; Zvolensky, Michael J.
Abstract: The present study investigated alcohol consumption and cigarettes per day in relation to smoking outcome expectancies among Spanish-speaking Latinx daily smokers ( N = 371). There was a significant interaction between alcohol consumption and number of cigarettes per day on positive smoking expectancies. Specifically, alcohol consumption has a stronger association with positive expectancies for smoking at lower rates of cigarettes per day. No such interaction was evident for negative consequence smoking expectancies. The current study highlights the potential importance of alcohol consumption and smoking rate for better understanding smoking outcome expectancies among Latinx smokers.